Dihydrochalcones with antiinflammatory activity from leaves and twigs of cyathostemma argenteum - Somsrisa J. (2014)
A new dihydrochalcone derivative, 4',6'-dihydroxy-2',4-dimethoxy-5'-(2''- hydroxybenzyl)dihydrochalcone (1) and one known dihydrochalcone, 4',6'-dihydroxy-2',4- dimethoxydihydrochalcone (2) were isolated from leaves and twigs of Cyathostemma argenteum. Their structures were established by spectral methods, mainly 2D NMR spectroscopic techniques, which involved combined applications of DEPT, COSY, HMQC and HMBC. The molecular structure of 1 was also confirmed by single crystal X-ray diffraction. The test compounds 1 and 2 displayed significant inhibitory activity at a dose of 1 mg/ear on edema formation at all determination times, with similar intensity as phenylbutazone. © 2013 by the authors.